Political corporate social responsibility: How business managers can hold office without election - Borges, A.; Ramalho, N. (29th EBES Conference - Lisbon, 2019)
Recent research has been considering engagement in Corporate Social Responsibility (CSR) as a political strategy adopted by organizations, and a new concept emerged linked to this idea: Political CSR (PCSR, Frynas & Stephens, 2015). Gradually, companies’ managerial background allied with ethical endeavors have been legitimizing them to perform a political role and to participate in political decision-making processes (Scherer & Palazzo, 2007). Despite the importance of the phenomenon, empirical research on this topic is very scarce. Also, the micro-level of PCSR has been neglected (Scherer, 2018). Therefore, based on a sample of 220 participants, we aim to verify the extent to which boards' political skill is positively related with political legitimacy, through the mediation effect of CSR. For this purpose, we conducted a multiple mediation data analysis (Preacher & Hayes, 2013), which showed that engagement in specific CSR practices, namely towards community, nature and future generations, as well as towards organizations’ employees, build business managers’ political legitimacy. Both full and partial mediations were found depending on the specific political skill of the board. Engagement in CSR practices towards customers and legal compliance showed no mediations whatsoever. We conclude that business managers’ political skill plays an important role since it facilitates the adoption of CSR an effective political strategy to hold office without election, thus supporting previous PCSR theoretical frameworks.